Bioassay Guided Fractionation of Senna singueana and Its Potential for Development of Poultry Phytogenic Feed Additives - Jambwa, Prosper; Makhubu, Fikile N.; Matope, Gift; Fouche, Gerda; McGaw, Lyndy J. (Frontiers in Veterinary Science, 2022)
There has been burgeoning interest in plant-based feed additives following restrictions placed on the use of antibiotic feed additives in many countries. Phytogenic feed additives are recommended to have a range of useful properties to support the growth and development of poultry to a similar level as that obtained by supplementing feed with antibiotics. The aim of this study was to evaluate the antibacterial, anti-lipoxygenase and antioxidant activity, and in vitro safety of fractions and isolated compounds from leaves of Senna singueana. Antibacterial activities of the fractions and isolated compounds were determined against a panel of bacteria using a two-fold serial microdilution assay and qualitative bioautography assays. Anti-lipoxygenase activity was evaluated using the ferrous oxidation-xylenol orange (FOX) method. Antioxidant activity was assessed qualitatively and quantitatively using radical scavenging assays. Dichloromethane and ethyl acetate fractions from solvent-solvent partitioning had the best antibacterial activity with MIC values ranging from 156-313 µg/ml. Fractions obtained from column chromatography had significant to weak antibacterial activity with MIC values ranging from 50–1250 µg/ml. Bioautography showed clear bands of bacterial inhibition, indicating the presence of a number of active compounds in several fractions. The ethyl acetate fraction and all the column fractions had potent anti-lipoxygenase activity with IC50 values of ≤2.5 µg/ml which were lower than that of quercetin (positive control), indicating anti-inflammatory potential. The ethyl acetate fraction and several column fractions had powerful antioxidant activity with IC50 values of ≤5 µg/ml in the ABTS assay. Cytotoxicity values against Vero kidney cells ranged from LC50 = 40.0 - 989.3µg/ml. Bioassay-guided fractionation led to the isolation and identification of a known bioactive compound, luteolin. S. singueana is a promising candidate for the development of poultry phytogenic feed additives.